Pelatihan Daring Pemanfaatan Jerami Padi Sebagai Media Tumbuh Pada Budidaya Jamur Merang - Tatang Sopandi (Jurnal Abadimas Adi Buana, 2021)
Desa Grinting, Kecamatan Tulangan, Kabupaten Sidoarjo is a rice farming area which in the harvest season is abundant and the rice straw is not used to generate added value economically. Farmers tend to be rice straw and often pollute the surrounding air. Cultivation of straw mushroom using straw as a growing medium is a viable option to overcome this problem. However, the people of Desa Grinting do not yet have sufficient knowledge and understanding to carry out a mushroom cultivation business. This training aims to increase the knowledge, understanding and interest of the people in Desa Grinting to carry out a straw mushroom cultivation business using rice straw as a growing medium. Training has been conducted using zoom and Whatapp applications for 2 months. The Youth Organization and GAPOKTAN members became target partners for this online training. During the training, the target partners were very active and enthusiastic about participating in the training, holding discussions and questions and answers. This courage training succeeded in increasing the knowledge, understanding and business interest of the target partners in cultivating edible mushrooms using straw as a growing medium. The real results in the form of behavior change were evident in the target partners and there were members who had done independent practice of making plant media using rice straw.